Does thrombolytic therapy harm or help in ST elevation myocardial infarction (STEMI) caused by the spontaneous coronary dissection? - Jović, Zoran; Obradović, Slobodan; Djenić, Nemanja; Mladenović, Zorica; Djurić, Predrag; Spasić, Marijan; Tavčiovski, Dragan (Vojnosanitetski pregled, 2015)
Introduction. Spontaneous coronary artery dissection (SCAD) is a very rare disease with poor prognosis. It mainly affects young women free of risk factors for coronary artery disease (CAD) and women during the peripartum period. The prognosis for myocardial infarction caused by SCAD is poor, management is often difficult and guidelines still missing. Case report. We presented a woman with acute myocardial infarction of anterior wall of the left ventricle, caused by spontaneous dissection of medial segment of the left anterior descending coronary artery. We treated the patient with thrombolytic therapy and performed coronary angiography after that. Finally we decided to do nothing more. Two years later we performed coronary angiography again and founded the coronary artery normal. We also analyzed 19 cases publiched from 1996 to 2012 when coronary artery dissection had been treated with thrombolytic agent. Analysis revealed only one case of 19, with complication after treating SCAD with thrombolysis. Conclusion. Sometimes, regarding myocardial infarction in young women with no risk factors for CAD, especially in young women in peripartum, we should think about SCAD. The presented case, like eight others, demonstrates that good clinical outcomes can be achieved with thrombolysis. In spite of all this, we still need more data to verify that thrombolysis does not have to harm the therapy for SCAD. For the time being thrombolytic therapy could be an option.